2018
DOI: 10.1111/imm.12919
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of autoimmune and anti‐tumour T‐cell responses by PTPN22

Abstract: A number of polymorphisms in immune-regulatory genes have been identified as risk factors for the development of autoimmune disease. PTPN22 (that encodes a tyrosine phosphatase) has been associated with the development of several autoimmune diseases, including type 1 diabetes, rheumatoid arthritis and systemic lupus erythematosus. PTPN22 regulates the activity and effector functions of multiple important immune cell types, including lymphocytes, granulocytes and myeloid cells. In this review, we describe the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 64 publications
(174 reference statements)
0
37
0
Order By: Relevance
“…This gene plays an important role in controlling the activity of various immune cells, especially B and T cells. Several studies have demonstrated an association between PTPN22 polymorphisms and the risk of T1D and other autoimmune diseases . However, the association of PTPN22 with LADA has not been widely explored.…”
Section: Discussionmentioning
confidence: 99%
“…This gene plays an important role in controlling the activity of various immune cells, especially B and T cells. Several studies have demonstrated an association between PTPN22 polymorphisms and the risk of T1D and other autoimmune diseases . However, the association of PTPN22 with LADA has not been widely explored.…”
Section: Discussionmentioning
confidence: 99%
“…The PTPN22 gene encodes the lymphoid phosphatase LYP (or PTPN22) that belongs to the protein tyrosine phosphatases (PTP) family and regulates the activity and effector functions of multiple immune cell types (Brownlie, Zamoyska, & Salmond, ). An additional gene located in the 1p13.2 region is RSBN1, whose ortholog in the mouse, Rsbn1 (also named Rosbin or KDM9), has been shown to encode the lysine‐specific histone demethylase 9 that specifically demethylates the dimethylated lysine 20 of histone H4 (H4K20me2), thereby modulating chromosome architecture (Brejc et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The protein tyrosine phosphatase non‐receptor type 22 gene ( PTPN22 ) encodes the lymphoid protein tyrosine phosphatase LYP, which is expressed exclusively in hematopoietic cells, including T and B cells . LYP is a potent negative regulator of T and B lymphocyte activation by modulating T‐cell receptor (TCR) and B‐cell receptor (BCR) signaling …”
Section: Introductionmentioning
confidence: 99%
“…In addition, overexpression of CD154 on T cells correlates with higher RA activity . To date, the functional role of the PTPN22 1858C>T polymorphism in autoimmune diseases is not entirely clear and its precise impact on signaling pathways is highly context dependent . Since the CD40/CD154 interaction promotes B‐ and T‐cell activation and cytokine secretion, the aim of this study was to evaluate the relationship between the 1858 T risk allele with CD40 and CD154 expression and IFN‐γ secretion in anti‐CCP‐positive RA patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation